Direct Air Capture of CO2 by Physisorbent Materials. Issue 48 (6th October 2015) - Kumar, Amrit; Madden, David G.; Lusi, Matteo; Chen, Kai‐Jie; Daniels, Emma A.; Curtin, Teresa; Perry, John J.; Zaworotko, Michael J.
Abstract: Sequestration of CO2, either from gas mixtures or directly from air (direct air capture, DAC), could mitigate carbon emissions. Here five materials are investigated for their ability to adsorb CO2 directly from air and other gas mixtures. The sorbents studied are benchmark materials that encompass four types of porous material, one chemisorbent, TEPA‐SBA‐15 (amine‐modified mesoporous silica) and four physisorbents: Zeolite 13X (inorganic); HKUST‐1 and Mg‐MOF‐74/Mg‐dobdc (metal–organic frameworks, MOFs); SIFSIX‐3‐Ni, (hybrid ultramicroporous material). Temperature‐programmed desorption (TPD) experiments afforded information about the contents of each sorbent under equilibrium conditions and their ease of recycling. Accelerated stability tests addressed projected shelf‐life of the five sorbents. The four physisorbents were found to be capable of carbon capture from CO2 ‐rich gas mixtures, but competition and reaction with atmospheric moisture significantly reduced their DAC performance. Abstract : Five benchmark materials are investigated for their ability to adsorb CO2 directly from air. It is found that physisorbents can compete with chemisorbents with respect to CO2 /N2 selectivity but direct air capture (DAC) performance is mitigated because of competition with water vapor. Optimizing pore size and pore chemistry in the presence of water vapor must be further addressed if physisorbents are to compete with chemisorbents.